Harry Potter and the cursed child. Parts one and two - Thorne, Jack; Rowling, J. K. Tiffany, John (Little, Brown London, 2016)
It was always difficult being Harry Potter and it isn't much easier now that he is an overworked employee of the Ministry of Magic, a husband, and a father of three school-age children. While Harry grapples with a past that refuses to stay where it belongs, his youngest son, Albus, must struggle with the weight of a family legacy he never wanted. As past and present fuse ominously, both father and son learn the uncomfortable truth: sometimes, darkness comes from unexpected places